Praktik Pencegahan Kecelakaan Anak di Lingkungan Rumah pada Ibu yang Mempunyai Anak Toddler di RW II Serangan Notoprajan Ngampilan Yogyakarta - Wulandari, Retno (STIKES 'Aisyiyah Yogyakarta, 2008)
Abstract: This descriptive research aims to examine practice of child’s accident prevention to mothers who have toddler in RW II Serangan Notoprajan Ngampilan Yogyakarta. Sample are all mothers in RW II Serangan on June 2008. The result of this research shows that level mother’s practice on child’s accident prevention are categorized enough (67,7%), less (19,4%) and good (12,9%)